THE APPLICATION OF LANGUAGE LEARNING STRATEGIES AND ITS CORRELATION WITH MOTIVATION OF THE STUDENTS OF BEC PARE - ARYANI, RETNO DWI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Language Learning Strategies include certain activities of learners to learn second or foreign languages more easily and effectively. There are some factors affecting the choice of strategies including motivation. Motivation can determine human behavior to do something by energizing the behavior. In this study, the writer conducted an analysis about learning strategies and motivation of the students of BEC Pare. This study is conducted to discover: (1) language learning strategies applied by the students of TC 120 BEC Pare; (2) the motivation of the students of TC 120 BEC Pare; and (3) the correlation between the use of learning strategies and motivation of the students of TC 120 BEC Pare. This study uses descriptive quantitative approach as it deals with the statistical data to analyze the language learning strategies and motivation and also the correlations between those two variables. The participants of the study are the students of Training Class (TC) program of Basic English Course (BEC) Pare in the period of TC 120. The writer used two instruments to collect the data: Strategy Inventory for Language Learning (SILL) questionnaire and Motivated Strategies for Language Questionnaire (MSLQ). This study reveals that Social Strategies are the most dominant learning strategies and Task Value is the most motivational orientation of the students of TC 120 BEC Pare. It shows that most students tend to work with others and consider their interest and the importance of the course in learning English. In addition, this study reveals that there is a moderate correlation between language learning strategies and motivation. Five categories of learning strategies, namely: Memory-related Strategies, Cognitive, Meta-cognitive, Affective, and Social Strategies are significantly correlated with five motivational orientations: Extrinsic Goal Orientation, Task Value, Control of Learning Beliefs, Self-efficacy for Learning and Performance, and Test Anxiety. The writer suggests the next researchers to do further studies on learning strategies and motivation related to the students’ achievement. She also suggests the teachers of TC Program of BEC Pare to be aware of the students’ learning strategies and motivation because the teachers can influence their students to be motivated by certain learning program and tasks.Keywords: learning strategies, Social Strategies, motivation, Task Value, Strategy Inventory for Language Learning (SILL) questionnaire, Motivated Strategies for Language Questionnaire (MSLQ).